Аналіз несиметричних режимів у шестиелектродній дуговій електропечі імпульсного струму - Гудим, В.; Дроздовскі, П.; Постолюк, А. (Технічна електродинаміка, 2012)
In six of the electrode for electric arc furnace pulsating current pu-order mathematical modeling studied mode coordinates and the energy characteristics of the most likely not symmetric modes of electric arc furnace.